Pilihan Terapi Infeksi Covid-19 Pada Anak - Joko Tri Atmojo; Rejo Rejo; Dewi Arradini; Aquartuti Tri Darmayanti; Aris Widiyanto (Poltekkes Kemenkes Surakarta, 2020)
Background: Not all Covid-19 infections in children are mild and show a good prognosis, so it is very important to define them as a vulnerable population. Information related to the treatment of Covid-19 infection in children is still very limited, so the authors are interested in conducting a systematic review to discuss and provide information related to various types of drugs and treatment of Covid-19 infection in children. Methods: A systematic database search was carried out in July 2020 through the PUBMED and Google Scholar databases. Keywords used include: